Terrores nocturnos: a noite e a estética noir em Edgar Allan Poe - Gil, Isabel Capeloa (2007)
Stemming from a discussion of the concept of scopic modernity, the article analyzes the night as the ultimate psycho-philosophical boundary, disrupted by the penetration of the technologies of light and vision in the 19th century. It further questions the changes prompted by this euphoric development in the subject’s relation to the modern world, particularly through the aesthetic model of the voyeur and its reflection in the work of Edgar Allan Poe, first, and in film noir, later. Through a representative analysis of two of Poe’s tales, this literary discourse is presented as a counter-narrative to the modern project. Without defending a causal nexus between the literary and the filmic, the article claims that this counter-narrative of scopic modernity is, however, remediated (Bolter/Grusin) in the aesthetics of film noir.